2019
DOI: 10.1111/tpj.14335
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interactions reveal the antagonistic roles of FT/TSF and TFL1 in the determination of inflorescence meristem identity in Arabidopsis

Abstract: Summary During the transition to the reproductive phase, the shoot apical meristem switches from the developmental program that generates vegetative organs to instead produce flowers. In this study, we examined the genetic interactions of FLOWERING LOCUS T (FT)/TWIN SISTER OF FT (TSF) and TERMINAL FLOWER 1 (TFL1) in the determination of inflorescence meristem identity in Arabidopsis thaliana. The ft‐10 tsf‐1 mutants produced a compact inflorescence surrounded by serrated leaves (hyper‐vegetative shoot) at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…This is expected since the bZIP mutations at the LFY locus prevent access of both TFL1 and of activating PEBP family members FT and the closely related TWIN SISTER OF FT (TSF). Indeed, it has been shown that the terminal flower phenotype of tfl1 is suppressed in tfl1 ft tsf triple mutants 49 .…”
Section: Resultsmentioning
confidence: 99%
“…This is expected since the bZIP mutations at the LFY locus prevent access of both TFL1 and of activating PEBP family members FT and the closely related TWIN SISTER OF FT (TSF). Indeed, it has been shown that the terminal flower phenotype of tfl1 is suppressed in tfl1 ft tsf triple mutants 49 .…”
Section: Resultsmentioning
confidence: 99%
“…The role of FT in flowering is mainly counteracted by the action of TERMINAL FLOWER 1 ( TFL1 ), a close homologue belonging to the CENTRORADIALIS (CEN)-like subfamily of proteins. Indeed, FT and TFL1 have antagonistic roles in the regulation of flowering across different plant species ( Seo et al , 2009 ; Pin et al , 2010 ; Wickland and Hanzawa, 2015 ; Wang et al , 2017 ; Kaneko-Suzuki et al , 2018 ; Lee et al , 2019 ; Wu et al , 2019 ). In Arabidopsis, rice, and soybean ( Glycine max ), TFL1 loss-of-function mutations cause early flowering and the generation of a terminal inflorescence ( Shannon and Meeks-Wagner, 1991 ; Liu et al , 2010 ; Repinski et al , 2012 ; Kaneko-Suzuki et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, rice, and soybean ( Glycine max ), TFL1 loss-of-function mutations cause early flowering and the generation of a terminal inflorescence ( Shannon and Meeks-Wagner, 1991 ; Liu et al , 2010 ; Repinski et al , 2012 ; Kaneko-Suzuki et al , 2018 ). At least in Arabidopsis and rice, FT proteins activate the expression of flowering genes, while members of the TFL1 protein family are involved in the transcriptional repression of genes activated by FT ( Kaneko-Suzuki et al , 2018 ; Lee et al , 2019 ). If a similar mechanism operates in quinoa, generating TFL1 loss-of-function mutations might be a simple alternative to FT mutagenesis to achieve early flowering phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…These include the photoperiodic, vernalization, ambient temperature, plant hormone, and autonomous owering pathways [1,[4][5][6][7][8][9][10]. Within these pathways, a number of genes have been identi ed as involved in owering time regulation, including CONSTANS-LIKE (COL) genes, phosphatidyl ethanolamine-binding protein (PEBP) genes and several members of MADS-Box gene family [1][2][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%